Selection and appointment of higher education leaders in Ethiopia: An assessment of implementation - Abebaw Yirga Adamu (Bahir Dar Journal of Education)
The Ethiopian Higher Education Proclamation (No. 650/2009) states that public higher education institutions have the autonomy to nominate top-level leaders. However, until recently the university community was not involved in the nomination and appointment of top level-leaders. In 2017, the Ministry of Education endorsed a new participatory, transparent and ?erit-based?strategy for selecting and appointing higher education leaders. This study assessed the implementation of the new leadership selection and appointment process mainly based on the experiences of the university community. The study was conducted at Bahir Dar University, one of the public universities in Ethiopia. The participants of the study were members of the search and selection committee, candidates for different leadership positions, and staff representatives who participated in the selection process. Participants were selected using purposive sampling technique. Data were collected through interview and document review and analyzed using deductive thematic analysis. The study revealed that the selection process ensures equality of opportunity and it is transparent from the outset to the end. However, there were issues which created confusion among the community, including eligibility of applicants, terms of office of the search and selection committee, point allocation for experience based on different ranges, number of candidates considered to be sufficient to run the selection process, and the procedure that needs to be followed if there are no enough applicants for a post. The study also showed concerns and discontent of the University community regarding the selection practice including staff underrepresentation in the selection process, the weight given to staff evaluation, and the emphasis given to promote women participation in leadership. It is also understood that the Directive is a necessary but not sufficient condition to promote ethnic diversity given the politicization of ethnicity in the country. The study necessitates the need for early intervention to address discontents and confusions.